Staphylococcus aureus CC30 Lineage and Absence of sed,j,r-Harboring Plasmid Predict Embolism in Infective Endocarditis - Rasigade, Jean-Philippe; Leclère, Amélie; Alla, François; Tessier, Adrien; Bes, Michèle; Lechiche, Catherine; Vernet-Garnier, Véronique; Laouénan, Cédric; Vandenesch, François; Leport, Catherine; , The AEPEI Study Group; Hoen, B.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Staphylococcus aureus induces severe infective endocarditis (IE) where embolic complications are a major cause of death. Risk factors for embolism have been reported such as a younger age or larger IE vegetations, while methicillin resistance conferred by the mecA gene appeared as a protective factor. It is unclear, however, whether embolism is influenced by other S. aureus characteristics such as clonal complex (CC) or virulence pattern. We examined clinical and microbiological predictors of embolism in a prospective multicentric cohort of 98 French patients with monomicrobial S. aureus IE. The genomic contents of causative isolates were characterized using DNA array. To preserve statistical power, genotypic predictors were restricted to CC, secreted virulence factors and virulence regulators. Multivariate regularized logistic regression identified three independent predictors of embolism. Patients at higher risk were younger than the cohort median age of 62.5y (adjusted odds ratio [OR] 0.14; 95% confidence interval [CI] 0.05 to 0.36). S. aureus characteristics predicting embolism were a CC30 genetic background (adjusted OR 9.734; 95% CI 1.53 to 192.8) and the absence of pIB485-like plasmid-borne enterotoxin-encoding genes sed, sej and ser (sedjr; adjusted OR 0.07; 95% CI 0.004 to 0.457). CC30 S. aureus has been repeatedly reported to exhibit enhanced fitness in bloodstream infections, which might impact its ability to cause embolism. sedjr-encoded enterotoxins, whose superantigenic activity is unlikely to protect against embolism, possibly acted as a proxy to others genes of the pIB485-like plasmid found in genetically unrelated isolates from mostly embolism-free patients. mecA did not independently predict embolism but was strongly associated with sedjr. This mecA-sedjr association might have driven previous reports of a negative association of mecA and embolism. Collectively, our results suggest that the influence of S. aureus genotypic features on the risk of embolism may be stronger than previously suspected and independent of clinical risk factors.